A KM-driven formative assessment framework to problem-solving for law academics teaching first year non-law students - Chandran, Kanchana; Sukumaran, Sanath; Chandran, Kalpana (2016)
This conceptual paper discusses the need for Knowledge Management (KM) intervention in strategising formative assessment for non-law students studying law.It proposes a unique approach through formative assessment to tailor an effective response to the challenges faced by law academics teaching first year non-law students. The research culminates with a formative assessment framework hereafter referred to as KMIRAC.The conceptual framework embodies tenets of KM manifested in two distinct stages, Stage 1 being the IRAC equation to problem-solving and Stage 2 being the critical elements of authentic assessment.Both stages 1 and 2 are aimed at assisting and providing law academics with a toolkit in teaching first year non-law students.